New evidence for the dating and impact of the Black Death in Asia - Hymes, Robert P.; Green, Monica Helen (Medieval globe ;, 2022)
Since 2014, when The Medieval Globe first presented the latest interdisciplinary scholarship on the Black Death as the first global pandemic, the pace and intensity of research has only intensified. This follow-up volume features two extended essays laying out evidence that the Second Plague Pandemic was already ravaging China by the second quarter of the thirteenth century--over a century before it made its virulent appearance in the greater Mediterranean region. In a core contribution, Robert Hymes presents an extensive analysis of Chinese medical texts, showing that physicians were adapting their terminology and treatments to the emergence of a virulent new disease: plague. In an overarching essay, Monica H. Green summarizes the state of our knowledge about the timing and expanse of the Black Death, to place it on the map of Asia and in the context of current debates.